VD_FINDINFO HC / 2019 / 1010 vom 9. Dezember 2019 - VD Tribunal cantonal (2019)
BAIL À LOYER, DÉFAUT DE LA CHOSE, ACTION EN DOMMAGES-INTÉRÊTSEN GÉNÉRAL, DOMMAGE, CHIFFRE D'AFFAIRES, PERTEARGENT | 8 CC, 259e CO